Heuristic PAC model for hybrid MTO and MTS production environment - Chang, SH; Pai, PF; Yuan, KJ; Wang, BC; Li, RK (My University, 2003)
Two distinct types of semiconductor plants in Taiwan are integrated device manufacturing (IDM) plants and foundry plants. Most IDM plants are make-to-stock (MTS) operations, focusing on throughput and machine utilization. However, foundry plants are make-to-order (MTO) operations, focusing on due date and cycle time. Besides the challenge of different process technology, the mode of hybrid operation (a combination of MTO and MTS operations) is also a formidable task for these plants. This study develops a heuristic production activity control model to achieve the two different criteria in a hybrid wafer production environment. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: wafer fabrication make-to-stock; make-to-order; production activity control; theory of constraints